Disparity in public funding of systemic therapy for metastatic renal cell carcinoma within Canada - Jackson, Emily B.; Hotte, Sebastien J. (Canadian Urological Association Journal, 2022)
Introduction: There have been significant advances in systemic therapies for metastatic renal cell carcinoma (mRCC). There are currently 11 drugs approved by Health Canada: sunitinib, sorafenib, pazopanib, axitinib, everolimus, temsirolimus, nivolumab, ipilimumab, cabozantinib, lenvatinib, and pembrolizumab. These novel medications have dramatically altered the prognosis and patient experience. Despite proven benefits and recommendations for funding of most of these drugs, public access has been uneven across Canadian provinces. Methods: We describe the provincial differences and timelines in public funding for approved systemic therapies for mRCC in Canada. Drug funding data was collected from the pan-Canadian Oncology Drug Review (pCODR) database and provincial drug formularies. Missing information was obtained from provincial cancer center pharmacists or drug formulary managers. We compared these dates to data available through regulatory bodies in the U.S., Europe, and Australia. Results: There have been significant differences in the dates of approval for public funding among the provinces, with lags spanning between two and 57 months. Funding approval was typically earlier in western provinces and those with denser populations, and most delayed in smaller, eastern provinces. Approval timelines in Canada were similar to those in the U.S., Europe, and Australia. Conclusions: Most drugs approved for use in mRCC are publicly funded for specific patient populations across Canada; however, we illustrate considerable disparities in public funding implementation across the Canadian provinces. These funding lags may create inequities and differences in the patient experience across the Canadian healthcare system.